2016
DOI: 10.1098/rspb.2016.0496
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation dominance and genomic-island acquisition ofBradyrhizobiumwith superior catabolic capabilities

Abstract: Root nodule-forming rhizobia exhibit a bipartite lifestyle, replicating in soil and also within plant cells where they fix nitrogen for legume hosts. Host control models posit that legume hosts act as a predominant selective force on rhizobia, but few studies have examined rhizobial fitness in natural populations. Here, we genotyped and phenotyped Bradyrhizobium isolates across more than 800 km of the native Acmispon strigosus host range. We sequenced chromosomal genes expressed under free-living conditions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 80 publications
(139 reference statements)
0
40
0
Order By: Relevance
“…Some rhizobia produce a cocktail of NFs that gives them access to diverse host species in which they frequently fix little or no nitrogen (Pueppke & Broughton, ). Other genotypes of rhizobia dominate host nodules and rhizospheres through mechanisms correlated with antibiotic resistance and catabolic flexibility, which can promote persistence in the soil (Hollowell et al ., , ,b). Finally, some rhizobia evade host control over nodulation specificity by hitchhiking into the nodule alongside NF‐secreting strains without themselves having any of the genes to encode NFs (Gano‐Cohen et al ., ).…”
Section: Control and Conflict Over Legume Nodulationmentioning
confidence: 99%
“…Some rhizobia produce a cocktail of NFs that gives them access to diverse host species in which they frequently fix little or no nitrogen (Pueppke & Broughton, ). Other genotypes of rhizobia dominate host nodules and rhizospheres through mechanisms correlated with antibiotic resistance and catabolic flexibility, which can promote persistence in the soil (Hollowell et al ., , ,b). Finally, some rhizobia evade host control over nodulation specificity by hitchhiking into the nodule alongside NF‐secreting strains without themselves having any of the genes to encode NFs (Gano‐Cohen et al ., ).…”
Section: Control and Conflict Over Legume Nodulationmentioning
confidence: 99%
“…; Hollowell et al . ). Phylogenetic relationships among isolates were reconstructed using the CHR and SI loci with PhyML 3.0 utilising a BioNJ starting tree and subtree pruning and regrafting (Guindon et al .…”
Section: Methodsmentioning
confidence: 97%
“…The CHR and SI genome regions were analysed separately because the SI can be horizontally transferred (Hollowell et al . ). For each isolate and for each genome region, genotype frequency was calculated as the proportion of isolates from the sampled population that were identified as the focal genotype (Hollowell et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…We delineate ecological differentiation using whole‐genome data of a widely distributed symbiotic nitrogen‐fixing soil bacteria ( Bradyrhizobium japonicum ) which associates with an endemic host legume ( Acacia acuminata ), spanning a climate gradient along a large heterogeneous geographical region in south‐western Australia. Previous studies have identified significant effects of soil chemistry, moisture content, and host demography on rhizobial abundance, diversity and fitness (Thrall et al , ; Hollowell et al ; van Ham et al ; Vuong et al ; Birnbaum et al ; Dinnage et al ), as well as host‐rhizobial co‐adaptation (Barrett et al ) and geographical variation in the functional outcomes of host–rhizobial interactions (Thrall et al ; Barrett et al ). Dispersal limitation has also been identified in Bradyrhizobium (Bissett et al ).…”
Section: Introductionmentioning
confidence: 99%